Grounded capacitor current-mode oscillator using single currentfollower - Abuelma’atti, M.T. (1992)
A new configuration for realizing a current-mode oscillator using single positive current-follower is presented. The circuit uses three grounded capacitors and three resistors. The feasibility of obtaining a quadrature oscillator is investigated